Effects of Plastic Mulching and Basal Nitrogen Application Depth on Nitrogen Use Efficiency and Yield in Maize - Wang, Xiukang; Wang, Ning; Xing, Yingying; Yun, Jia; Zhang, Huihui (Frontiers in Plant Science, 2018)
The demand for increased grain production to support population and consumption growth has led to increased interest in field management approaches that incorporate plastic mulching and fertilization management. The purpose of this study was to investigate the effects of plastic mulching and basal nitrogen (N)-fertilizer application depth on N balance estimations, N use efficiency (NUE) and maize yield. The experiment was conducted in 2014 and 2015 with six treatments: no N fertilizer and no mulching (CK), traditional broadcast N fertilizer with mulching (T0), basal N-fertilizer application at a depth of 6 cm with no mulching (T1), basal N-fertilizer application at a depth of 6 cm with plastic mulching (T2), basal N-fertilizer application at a depth of 12 cm with no mulching (T3) and basal N-fertilizer application at a depth of 12 cm with plastic mulching (T4). Mulching and basal N-fertilizer application depth each had significant effects on grain yield, but there were no significant interactions between them. The highest grain yield was observed in the T2 treatment and was 89.1% and 99.8% higher than the grain yield in the CK treatment in 2014 and 2015, respectively. The N uptake in T2 was 21.3% and 25.3% higher than that in the T0 treatment in 2014 and 2015, respectively. Relative to the value in the T0 treatment, the mean N loss over the two years was reduced by 34.6% in T2 and by 39.8% in T4. The basal N-fertilizer application depth of 12 cm yielded an obvious increase in NUE, but a high N residual remained below 50 cm after harvest, indicating the higher potential for N losses. In addition, the field application of this type of fertilizer management would require more labour in the absence of the implementation of mechanization. Based on the results, basal N-fertilizer application a depth of 6 cm without plastic mulching is recommended because it significantly increased grain yield and NUE, reduced N loss and requires no investment in plastic film, which are conducive to food security and environmental conservation.